Posterior annulus shortening increases leaflet coaptation in ischemic mitral incompetence: a new and valid technique - Hetzer, Roland; Solowjowa, Natalia; Siniawski, Henryk; Delmo Walter, Eva Maria (Annals of Cardiothoracic Surgery, 2015)
Background: We introduce a technique of posterior annulus shortening to augment leaflet coaptation which addresses the restrictive mitral leaflet mobility in ischemic mitral incompetence (IMI), and report its long-term outcome. Methods: Between 1992 and 2012, 75 patients (mean age, 64.6±10.4 years; median, 66.0 years; range, 35.0-86.1 years) underwent repair of IMI by posterior annulus shortening to augment leaflet coaptation surface area. This technique reduces the annular diameter to between 23 and 25 mm and decreases the valve orifice to between 3.5 to 4.5 cm2, which is sufficient to ensure an adequate leaflet coaptation area. An untreated pericardial strip is used to reinforce the shortened annulus in order to avoid redilatation. This augments the posterior leaflet by increasing the ratio of leaflet area/valve orifice where the coaptation gap is the greatest. The tissue strip increases and heightens the area which the posterior leaflet offers to the anterior leaflet for coaptation during closure, making valve closure possible in advanced leaflet restriction. Results: During a mean follow-up of 7.62±0.66 (median 8.53, range, 3.6-20.9) years, New York Heart Association (NYHA) functional class significantly improved, left ventricular ejection fraction (LVEF) increased and there was a tremendous abatement of MI (P